Regulation of sirtuin expression in autoimmune neuroinflammation: Induction of SIRT1 in oligodendrocyte progenitor cells. (21st June 2019) - Prozorovski, Tim; Ingwersen, Jens; Lukas, Denise; Göttle, Peter; Koop, Barbara; Graf, Jonas; Schneider, Reiner; Franke, Kristin; Schumacher, Stefan; Britsch, Stefan; Hartung, Hans-Peter; Küry, Patrick; et al.
Highlights: SIRT1 protein level and enzymatic activity are induced in OPCs in EAE. Blockade of SIRT1 activity enhances mitotic activity of cultured OPCs but did not affect the capacity to differentiate. SIRT1 inhibition may emerge as a novel regenerative approach directed to expand the OPC pool. Abstract: In multiple sclerosis (MS) regeneration of oligodendrocytes following inflammatory demyelination is limited by the compromised ability of progenitors to repopulate lesioned areas and transition to functionally competent oligodendrocytes. Regarding underlying mechanisms, the involvement of epigenetic processes has been suggested, e.g. the contribution of histone deacetylases (HDAC) known to regulate oligodendrocyte progenitor cell (OPC) differentiation. However, their precise expression patterns, particular of redox-sensitive NAD + HDACs, remains largely unknown. In this study, we determined the expression and activity of sirtuins, members of the HDAC class III family with a specific focus on SIRT1, previously associated with neurodegenerative, inflammatory and demyelinating disorders of the central nervous system (CNS). By investigating mouse experimental autoimmune encephalomyelitis (EAE), a model for MS, we found that transcription of SIRT1, SIRT2 and SIRT6 was significantly increased in the CNS during chronic disease stages. We confirmed this finding for SIRT1 protein expression and were able to localize upregulated SIRT1 in nuclei of NG2 + or PDGFRα + OPCs in demyelinated brain lesions. In cultured mouse A2B5 + OPCs blockade of SIRT1 activity by the small molecule compound Ex527 enhanced mitotic activity but did not affect the capacity to differentiate. A similar pattern was detectable in OPCs derived from SIRT1-deficient animals. Taken together, our data suggest that SIRT1 inhibition may help to expand the endogenous pool of OPCs without affecting their differentiation.